2010
DOI: 10.5539/jas.v2n3p17
|View full text |Cite
|
Sign up to set email alerts
|

Oxygation Improves Yield and Quality and Minimizes Internal Fruit Crack of Cucurbits on a Heavy Clay Soil in the Semi-arid Tropics

Abstract: Lack of oxygen due to sustained wetting fronts associated with drip and subsurface drip irrigated crops in heavy clay soil can negatively impacts on yield, fruit quality and water use efficiency of cucurbit crops. This study evaluated the effects of aerated irrigation water (oxygation) with subsurface drip irrigation, employing an in-line air injector (Mazzei venturi to introduce 12% air by volume of water) on fruit yield, quality and water use efficiency of watermelon (Citrullus vulgaris) and pumpkin (Cucurbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our previous studies had shown that soil aeration at different growth stages lead to higher quality of potted tomatos30. Consistent with Bhattarai et al 53,. significantly greater total soluble solid cucurbits were reported in the aeration treatments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous studies had shown that soil aeration at different growth stages lead to higher quality of potted tomatos30. Consistent with Bhattarai et al 53,. significantly greater total soluble solid cucurbits were reported in the aeration treatments.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the effects on fruit appearance, aeration is known to influence the quality and taste2653. Our previous studies had shown that soil aeration at different growth stages lead to higher quality of potted tomatos30.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial soil aeration can enhance air permeability and improve soil oxygen content, effectively relieving hypoxic stress on roots (Bhattarai et al, 2006(Bhattarai et al, , 2008(Bhattarai et al, , 2010Chen et al, 2011;Pendergast et al, 2013) while maintaining soil microorganism and enzyme activities (Niu et al, 2012b). Thus, soil moisture and soil aeration are coupled, and the soil water content influences soil aeration (Boone et al, 1986).…”
mentioning
confidence: 99%
“…Supplemental soil aeration is also possible either along with the water (termed as aerated irrigation) or separately, and can effectively improve the oxygen level in rhizosphere. Studies have shown that these practices can be very useful in overcoming problems associated with hypoxia in the root zone of irrigated crops over a range of crops, soil water contents and soil types, and for improving crop performance under oxygen-deficient conditions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%